1998
DOI: 10.1007/bf03189351
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of milnacipran in liver impairment

Abstract: The pharmacokinetics of single 50 mg oral and intravenous doses of milnacipran, a new non tricyclic antidepressant drug, were compared in 11 chronic liver impaired (LI) subjects and in 6 control subjects. Hepatic impairments, classified according to the PUGH scale were moderate (1 grade A), intermediate (6 grade B) and severe (4 grade C). Concentrations of unchanged drug and its conjugated form (its main metabolite) were measured in plasma and urines. In control subjects, milnacipran present high absolute bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 5 publications
0
24
0
5
Order By: Relevance
“…A major milnacipran metabolite, previously reported as milnacipran N-glucuronide (Puozzo et al, 1998), was ultimately identified in this study as l-milnacipran carbamoyl O-glucuronide. This major metabolite was excreted primarily in urine and accounted for approximately 17% of the dose.…”
Section: Discussionmentioning
confidence: 78%
“…A major milnacipran metabolite, previously reported as milnacipran N-glucuronide (Puozzo et al, 1998), was ultimately identified in this study as l-milnacipran carbamoyl O-glucuronide. This major metabolite was excreted primarily in urine and accounted for approximately 17% of the dose.…”
Section: Discussionmentioning
confidence: 78%
“…Sensitivity is sufficient to quantify milnacipran in patients (50 mg b.i.d.) over at least four to five half-lives [8][9][10]. A typical pharmacokinetic profile of a subject administered 50 mg oral single dose is shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of a low cost bioanalytical method, easy to transfer and to set up, represents an advantage in therapeutic drug monitoring when required (control of compliance, overdose). The current method was used throughout the development of milnacipran and is, therefore, a pivotal reference when using pharmacokinetic data from major published trials [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…28 Pharmacokinetic studies indicate that dose adjustment is not necessary based on age, gender, mild-to-moderate renal impairment, 29 or mild-to-moderate hepatic impairment. 30 However, caution should be exercised in patients with moderate renal impairment or severe hepatic impairment. In patients with severe renal impairment, the maintenance dose of milnacipran should be reduced by approximately 50% to 50 mg/day (25 mg twice daily).…”
Section: Pharmacologymentioning
confidence: 99%